2014
DOI: 10.1183/09031936.00034714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of exercise intolerance in Global Initiative for Chronic Obstructive Lung Disease grade 1 COPD

Abstract: The purpose of this study was to determine if a dissociation existed between respiratory drive, as estimated by diaphragmatic electromyography (EMGdi), and its pressure-generating capacity during exercise in mild chronic obstructive pulmonary disease (COPD) and whether this, if present, had negative sensory consequences.Subjects meeting spirometric criteria for mild COPD (n516) and age and sex-matched controls (n516) underwent detailed pulmonary function testing and a symptom limited cycle test while detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
152
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(161 citation statements)
references
References 36 publications
5
152
1
3
Order By: Relevance
“…This latter contention is supported by previous findings that bronchodilators, by decreasing lung hyperinflation, allow greater VT expansion during exercise even in mild COPD [20,21]. GUENETTE et al [19] reported that EMGdi was markedly higher at rest and throughout cycle exercise in mild COPD compared with healthy controls. The ratio of EMGdi to diaphragmatic pressure (Pdi) was also significantly higher relative to controls, indicating some degree of neuromuscular dissociation of the diaphragm.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…This latter contention is supported by previous findings that bronchodilators, by decreasing lung hyperinflation, allow greater VT expansion during exercise even in mild COPD [20,21]. GUENETTE et al [19] reported that EMGdi was markedly higher at rest and throughout cycle exercise in mild COPD compared with healthy controls. The ratio of EMGdi to diaphragmatic pressure (Pdi) was also significantly higher relative to controls, indicating some degree of neuromuscular dissociation of the diaphragm.…”
supporting
confidence: 56%
“…Patients with moderate-to-severe COPD have been shown to present with an EMGdi of 70% of maximum at peak incremental exercise [23], which corresponds to a V´E of around 32±10 L·min −1 using the same catheter as used in the study by JOLLEY et al [18]. At a similar absolute V´E, GUENETTE et al [19] found that patients with mild COPD have an EMGdi of 37% of maximum, suggesting that respiratory neural drive increases dramatically with advancing COPD severity. This is supported by data from patients with severe COPD who showed a reduction in the inspiratory discharge rate of single motor units recorded from the costal diaphragm following lung volume reduction surgery [24].…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Accumulating evidence suggests that neural respiratory drive (and 'central corollary discharge') is the proximate source of dyspnea during exercise in health [74,75,81] and in patients with COPD [63,82,83]. It follows that preservation of the EMGdi,rms%max-work rate relationship during incremental treadmill vs. cycle exercise testing in our study was primarily responsible for preservation of the dyspnea intensity (and unpleasantness)-work rate relationship, despite significant differences in V E and contractile respiratory muscle effort (pressure) requirements.…”
Section: Resultsmentioning
confidence: 99%
“…In their small but elegant physiological study, the authors compared the trajectory of dyspnoea rating, dynamic lung mechanics and the response of respiratory muscles to the inspiratory neural drive, as obtained during a standard incremental symptom-limited cycle ergometry in smokers and healthy age-matched nonsmokers. They concluded that the increased dyspnoea perception and associated reduced exercise capacity (25% lower maximal oxygen consumption reached in the incremental test), as recorded in smokers who do not meet the criteria for COPD, are explained by the increased mechanical load of the respiratory system: these patients have a preserved and appropriate ventilatory response, which is not usually the case in individuals developing COPD even at a mild stage [8]. In particular, the difference in dyspnoea intensity between smokers and healthy control subjects, as assessed by the Borg scale at a comparable workload (80 W), is close to 2.0 Borg units, which is likely to be sensitive from a clinical point of view.…”
Section: @Erspublicationsmentioning
confidence: 99%